Data integration in cardiac electrophysiology ablation toward achieving proper interoperability in health information systems - Hadi Kazemi-Arpanahi; Mostafa Shanbehzadeh; Esmat Mirbagheri; Abdolvahab Baradaran (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Providing information exchange and collaboration between isolated information systems (ISs) is essential in the health-care environments. In this context, we aimed to develop a communication protocol to facilitate better interoperability among electrophysiology study (EPS)-related ISs in order to allow exchange unified reporting in EPS ablation. MATERIALS AND METHODS: This study was an applied-descriptive research that was conducted in 2019. To determine the information content of agreed cardiac EPS Minimum Data Set (MDS) in Iran, the medical record of patients undergoing EPS ablation procedure in the Tehran Heart Center (THC) hospital was reviewed by a checklist. Then, an information model based on Health Level Seven, Clinical Document Architecture (HL7 CDA) standard framework for structural interoperability has been developed. In this framework, using NPEX online browser and MindMaple software, a set of terminology mapping rules was used for consistent transfer of data between various ISs. RESULTS: The information content of each data field was introduced into the heading and body sections of HL7 CDA document using Systematized Nomenclature of Medicine - Clinical Terminology names and codes. Then, the ontology alignment was designed in the form of thesaurus mapping routes. CONCLUSION: The sensitive, complex, and multidimensional nature of cardiovascular conditions requires special attention to the interoperability of ISs. Designing customized communication protocols plays an important role in improving the interoperability, and they are compatible with the needs of future Iranian health information exchange.